Hypocalcemic cardiomyopathy: a rare presenting manifestation of hypoparathyroidism. Issue 9 (12th September 2019) - Saini, Neharika; Mishra, Sanat; Banerjee, Saurav; Rajput, Rajesh
Abstract : Hypoparathyroidism patients present with features of hypocalcemia like carpopedal spasm, numbness and paresthesias but hypocalcemic cardiomyopathy leading to congestive heart failure (CHF) is a rare presentation. We present here a case of 55-year-old Asian man who was a known case of dilated cardiomyopathy for 6 months, presented with the chief complaints of shortness of breath on exertion and decreased urine output. On general physical examination, features suggestive of CHF were seen. Chvostek and Trousseau's sign was positive. The patient had a history of cataract surgery of both eyes 15 years ago. Further investigations revealed hypocalcemia. Echo showed severe global hypokinesia of left ventricle with left ventricle ejection fraction 15%. This CHF was refractory to conventional treatment, though, with calcium supplementation, the patient improved symptomatically. On follow-up after 3 months, an improvement was seen in the echocardiographic parameters with ejection fraction improving to 25%.